Aspekty technologiczne a funkcjonowanie systemu HACCP w przedsiębiorstwie przemysłu żywnościowego na przykładzie Mleczarni "Turek" Sp. z o.o. - Krysztoforska, Katarzyna; Lesiów, Tomasz (Technological Aspects Versus Functioning of HACCP System in a Food Company on the Example of the Dairy "Turek" Sp. z o.o., 2007)
The aim of the article is to present functioning of the HACCP system in the production of natural cheese Camembert in the Dairy "Turek" Sp. z o.o. The principles and procedures of HACCP implemented in the company, complexity of technological process and description of product properties are all those conditions which should be continuously and precisely controlled to guarantee quality and nutritional value of cheese Camembert. The relations between the production processes of natural cheese Camembert and functioning of HACCP system resulted not only from principles and procedures of the system but also from proper training of all workers. The list of CCP and potential health risks with methods for their monitoring, controlling and verifying give the scale of danger when the principles of personal hygiene and hygiene of production halls are not kept. On the basis of workers opinion poll it was proven that technological process can proceed properly if all procedures resulting from the HACCP system are obeyed and when it is supported by knowledge, substantiality, and involvement of all workers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Technologia (12); 2007; nr 1172, s. 59-79